Chemical Vapor Synthesis Of WC-Co Nanocomposite Powders - Manolete Mena (The Minerals, Metals and Materials Society, 2006)
WC-Co nanocomposite powder is among the first group of materials with a promising potential for nanocrystalline-materials application. A chemical vapor synthesis (CVS) process that has previously been used for preparing the aluminides of titanium and nickel, and other metallic and intermetallic powders has been applied to the preparation of WC-Co nanocomposite powder. This CVS system was designed so that a tungsten precursor (WCl6 powder) and a cobalt precursor (CoCl2 powder) were separately fed into each evaporator in a reactor by means of specially designed powder feeders. The reduction and carburization of the vaporized chlorides by methane-hydrogen mixtures produced nanosized WC and Co composite powder. The product is a very uniform mixture of the constituent powders, which is important to ensure a high quality of the bulk cemented tungsten carbide product after consolidation. In the present work, the effects of reaction temperature, CH4 to WCl6 ratio, CH4 to H2 ratio, residence time, and Co content on the powder composition and particle size were determined. The products were characterized using XRD, carbon analyzer, and TEM.